Rational design of artificial genetic switches : co-option of H-NS-repressed operons by the VirB virulence master regulator - Kane, Kelly (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2012)
The H-NS protein represses the transcription of hundreds of genes in Gram-negative bacteria. De-repression is achieved by a multitude of mechanisms, many of which involve binding of a protein to DNA at the repressed promoter in a manner that compromises the maintenance of the H-NS-DNA nucleoprotein repression complex. The principal virulence gene promoters in Shigella flexneri, the cause of bacillary dysentery, are repressed by H-NS. Expression occurs via a regulatory cascade whereby the AraC-like protein VirF activates an intermediate regulator VirB, which in turn derepresses the operons that encode the main structural components and the effector proteins of the S.flexneri type III secretion system. Bioinformatic analysis suggests that VirB , a protein that closely resembles members of the ParB family of plasmid partitioning proteins, has been co-opted into its current role as an H-NS antagonist in S. Jlexneri through genetic rearrangements that positioned a binding site for VirB at a location where it could act to disrupt H-NS repression.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.